2020
DOI: 10.1111/1759-7714.13415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short‐term outcomes following minimally invasive versus open Sweet esophagectomy for Siewert type II adenocarcinoma of the esophagogastric junction

Abstract: Background: Surgical resection is still the main treatment option for patients with resectable Siewert type II adenocarcinoma of the esophagogastric junction (AEG). This retrospective study evaluated the significance of minimally invasive Sweet esophagectomy (MISE) for the treatment of Siewert type II AEG. Methods: We retrospectively evaluated 174 patients with Siewert type II AEG who received a Sweet esophagectomy in our center between October 2013 and September 2017. Of these patients, 73 underwent MISE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Another study confirmed that paeonol upregulates miR-141 via the PKCδ and c-Src pathways to inhibit migration and invasion of cancer cells ( Horng et al, 2014 ). Furthermore, paeonol’s inhibition of cell migration is inseparable from inhibiting the PI3K/AKT signaling pathway, and this effect can be reversed by upregulating miR-21 and downregulating miR-424–3p ( Sun et al, 2020 ; Yang et al, 2022 ). Inflammatory cytokines and active substances in the tumor inflammatory microenvironment can activate various pathways that induce EMT and promote cancer cell migration ( Tan et al, 2021 ).…”
Section: Paeonol Anticancer Effectsmentioning
confidence: 99%
“…Another study confirmed that paeonol upregulates miR-141 via the PKCδ and c-Src pathways to inhibit migration and invasion of cancer cells ( Horng et al, 2014 ). Furthermore, paeonol’s inhibition of cell migration is inseparable from inhibiting the PI3K/AKT signaling pathway, and this effect can be reversed by upregulating miR-21 and downregulating miR-424–3p ( Sun et al, 2020 ; Yang et al, 2022 ). Inflammatory cytokines and active substances in the tumor inflammatory microenvironment can activate various pathways that induce EMT and promote cancer cell migration ( Tan et al, 2021 ).…”
Section: Paeonol Anticancer Effectsmentioning
confidence: 99%
“…Carcinoma of the esophagogastric junction (CEGJ) is defined as a carcinoma whose center is located within 5 cm above and below the esophagogastric anatomical junction and crosses the esophagogastric junction (EGJ). Due to the short and narrow EGJ site and the up-and-down invasive nature of the CEGJ, its biological behavior is different from that of gastric or esophageal cancer[ 1 - 3 ]. The Siewert staging, which is widely accepted in academia, classifies CEGJ into types I, II, and III based on the distance between the tumor center and the EGJ[ 4 ].…”
Section: Introductionmentioning
confidence: 99%